2022
DOI: 10.1097/md.0000000000032461
|View full text |Cite
|
Sign up to set email alerts
|

C.487C>T mutation in PAX4 gene causes MODY9: A case report and literature review

Abstract: Rationale: Maturity-onset diabetes of the young (MODY) is a group of autosomal dominant monogenic diabetes mellitus with a wide range of clinical manifestations that require distinct treatment strategies. MODY9 (OMIM # 612225) is a rare type of MODY, caused by a mutation in the Paired box gene 4 (PAX4). Patient concern: A 19-months boy was admitted to the department of endocrinology at Beijing Children’s Hospital due to excessive water drinking, polyuria for over half a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Subsequently, references of included articles were manually screened for relevant articles (Figure 1). This research revealed 21 cases [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A case report we have recently published was added to the analysis [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, references of included articles were manually screened for relevant articles (Figure 1). This research revealed 21 cases [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A case report we have recently published was added to the analysis [22].…”
Section: Methodsmentioning
confidence: 99%
“…1). This research revealed 21 cases [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A case report we have recently published was added to the analysis [22].…”
Section: Methodsmentioning
confidence: 99%
“…This mutation co-segregates with diabetes in a MODY9 family, in which several members have severe diabetic complications including retinopathy, nephropathy, and end-stage renal failure [15]. Furthermore, a recent case report reveals that an infant patient presenting with polydipsia and polyuria possesses a rare C.487C>T heterozygous missense mutation in the 7th exon region of the PAX4 gene, leading to an R163W variation that is associated with MODY9 [58].…”
Section: The Role Of Pax4 In the Development Of Diabetesmentioning
confidence: 99%
“…However, single gene mutations resulting in diabetes termed Maturity onset diabetes of the young have also been identified [ 5 ]. This involved genes such as glucokinase (GCK) [ 6 ], hepatocyte nuclear factor 1 alpha (HNF1A) [ 7 ], hepatocyte nuclear factor 1 alpha (HNF4A) [ 8 ], hepatocyte nuclear factor 1 beta ( HNF1B ) [ 9 ], sulfonylurea receptor 1 (ABCC8) [ 10 ], Insulin (INS), Neuronal differentiation 1 (NEUROD1) [ 11 ], insulin gene promoter factor 1 (IPF1 or PDX1) [ 12 ], Paired box 4 (PAX4) [ 13 ], ATP-binding cassette sub-family C member 8 (ABCC8), GATA binding protein 4 (GATA4) [ 14 ] and GATA binding protein 6 (GATA6) [ 15 ]. Potassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) [ 16 ], kruppel-like factor 11 (KLF11) [ 17 ], carboxyl ester lipase (CEL) [ 18 ], B lymphoid tyrosine kinase (BLK) [ 19 ], Adaptor protein, phosphotyrosine interacting with PH domain and leucine zipper 1 (APPL1) [ 20 ] Previous human genetic studies have demonstrated a correlation between the genetic mutations and T2DM, such as lamin A/C mutations [ 21 ], glucokinase regulatory protein (GCKR) [ 22 ], fat mass and obesity-associated gene (FTO) [ 23 ], monocarboxylate transporter 11(SLC16A11) [ 24 ], hematopoietically-expressed homeobox (HHEX) gene [ 25 ], transcription factor 7-like 2 (TCF7L2) [ 26 ], Pro12Ala polymorphism in peroxisome proliferator-activated receptor- γ (PPAR- γ ) [ 27 ] and others.…”
Section: Introductionmentioning
confidence: 99%